The use of score for neonatal acute physiology perinatal extention II (SNAPPE II) in predicting neonatal outcome in neonatal intensive care unit - Mia R A; Risa Etika; Agus Harianto; Fatimah Indarso; Sylviati M Damanik (Paediatrica Indonesiana, 2005)
Background Scoring systems which quantify initial risks have animportant role in aiding execution of optimum health services by pre-dicting morbidity and mortality. One of these is the score for neonatalacute physiology perinatal extention (SNAPPE), developed byRichardson in 1993 and simplified in 2001. It is derived of 6 variablesfrom the physical and laboratory observation within the first 12 hoursof admission, and 3 variables of perinatal risks of mortality.Objectives To assess the validity of SNAPPE II in predicting mor-tality at neonatal intensive care unit (NICU), Soetomo Hospital,Surabaya. The study was also undertaken to evolve the best cut-offscore for predicting mortality.Methods Eighty newborns were admitted during a four-month periodand were evaluated with the investigations as required for the specifi-cations of SNAPPE II. Neonates admitted >48 hours of age or afterhaving been discharged, who were moved to lower newborn care <24hours and those who were discharged on request were excluded. Re-ceiver operating characteristic curve (ROC) were constructed to derivethe best cut-off score with Kappa and McNemar Test.Results Twenty eight (35%) neonates died during the study, 22(82%) of them died within the first six days. The mean SNAPPE IIscore was 26.3+19.84 (range 0-81). SNAPPE II score of thenonsurvivors was significantly higher than the survivors(42.75+18.59 vs 17.4+14.05; P=0.0001). SNAPPE II had a goodperformance in predicting overall mortality and the first-6-daysmortality, with area under the ROC 0.863 and 0.889. The best cut-off score for predicting mortality was 30 with sensitivity 81.8%,specificity 76.9%, positive predictive value 60.0% and negativepredictive value 90.0%.Conclusions SNAPPE II is a measurement of illness severity whichcorrelates well with neonatal mortality at NICU, Soetomo Hospital.The score of more than 30 is associated with higher mortality